What Is Comparative Religion Comparing?: the Subject Matter of "Religious" Studies - Gualtieri, Antonio R. (Journal for the scientific study of religion, 1967)
What is the subject matter of the study of religion? Is it the external expression of religious persons and communities, i.e., the historical deposit of sacred scriptures, theologies, social institutions, ethical and liturgical prescriptions and practices? Accurate observation and description of these data and analysis to detect common structures are important and necessary. This is not, however, primary, since it excludes from its purview the personal meaning these external traditions possess for their participants. This objection suggests that enquiry should focus on the existential selfhood of individual communicants. Yet this, also, is unsatisfactory because it restricts study to the psychology of individuals. Research should concentrate, instead, on religious faith, i.e., existential selfhood or personal faith as this is evoked and expressed by an historical tradition. This entails discerning how items in a cumulative religious tradition enter into the believer's faith or selfhood by being existentially interpreted.